(untitled) - Shoham, Yoav (San Francisco, California, 1994)
This is book contens: On prolog, search, backward-chaining methods, other rule-based methods, truth maintenance systems, contraint satisfaction...
Keywords: Artificial intelligence,Prolog ( computer program language ); Data processing